Evaluating solid waste landfill site selection using multi-criteria decision analysis and geographic information systems in the city of Elazig, Turkey - Celiker, Murat; Yildiz, Osman; Nacar Kocer, Nilufer (Pamukkale Univ, 2019)
Solid waste landfill site selection is a relatively complex process and depends on several criteria and official regulations. In this study, the suitability of solid waste landfill site selection for the city of Elazig, Turkey, was determined by Multi-Criteria Decision Analysis (MCDA) and Geographic Information Systems (GIS). For this purpose, nine different criteria, namely distance from residential areas, distance from roads, distance from rivers, distance from spring wells, geology, slope, aspect, land capability classification and land use, were taken into consideration and their degrees of relative importance were defined via MCDA and the schematic maps for each criterion were prepared with GIS applications. The final landfill site suitability map for the study area was obtained by the overlay analysis tool of ArcGIS 9.3. The study results reveal that the landfill suitability index values for the selected site range between 2.64 and 6.10. The major part of the landfill site has relatively low index values implying that the selected site is suitable for solid waste landfill.
Keywords: Solid waste landfill site; multi-criteria decision; Landfill site suitability index; Geographic information systems; Analytic hierarchy process; Elazig